2018
DOI: 10.1126/scitranslmed.aao0144
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase activity governs diastolic dysfunction through a nongenomic mechanism

Abstract: There are no approved drugs for the treatment of heart failure with preserved ejection fraction (HFpEF), which is characterized by left ventricular (LV) diastolic dysfunction. We demonstrate that ITF2357 (givinostat), a clinical-stage inhibitor of histone deacetylase (HDAC) catalytic activity, is efficacious in two distinct murine models of diastolic dysfunction with preserved EF. ITF2357 blocked LV diastolic dysfunction due to hypertension in Dahl salt-sensitive (DSS) rats and suppressed aging-induced diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 42 publications
5
114
1
1
Order By: Relevance
“…There are 2 families of enzymes that regulate acetylation: lysine acetyl transferases (KATs, also known as histone acetyltransferases) reversibly acetylate lysine, and lysine deacetylases (KDACs, also known as histone deacetylases) remove acetyl groups from lysines. While the identity of the sarcomeric KATs and KDACs, as well as their target-site specificity, have yet to be determined, Jeong et al (2018) recently demonstrated that myofibrils treated, ex vivo, with p300 (a promiscuous acetyltransferase), increased sarcomeric acetylation and accelerated relaxation [14]. Thus, sarcomeric acetylation is sufficient to modulate contractile dynamics, though the precise sarcomeric acetylation sites that can impact myofilament contractility have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…There are 2 families of enzymes that regulate acetylation: lysine acetyl transferases (KATs, also known as histone acetyltransferases) reversibly acetylate lysine, and lysine deacetylases (KDACs, also known as histone deacetylases) remove acetyl groups from lysines. While the identity of the sarcomeric KATs and KDACs, as well as their target-site specificity, have yet to be determined, Jeong et al (2018) recently demonstrated that myofibrils treated, ex vivo, with p300 (a promiscuous acetyltransferase), increased sarcomeric acetylation and accelerated relaxation [14]. Thus, sarcomeric acetylation is sufficient to modulate contractile dynamics, though the precise sarcomeric acetylation sites that can impact myofilament contractility have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Control hearts were obtained from unused donor hearts that could not be used for transplantation. Myofibril mechanics were quantified using the fast solution switching technique (38). Details are provided in SI Appendix, Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Myofibrils were isolated from flash frozen soleus and tibialis anterior as described (35,36). A small section of muscle was cut into thin slices and bathed in 0.05% Triton X-100…”
Section: Myofibril Isolationmentioning
confidence: 99%
“…Myofibrils were isolated and mechanical parameters were measured as described (36)(37)(38). Myofibrils were placed on a glass coverslip in relaxing solution at 15°C and then a small bundle of myofibrils was mounted on two microtools.…”
Section: Myofibril Mechanicsmentioning
confidence: 99%